Entre sagas, agruras e duelos: uma análise comparativa da bela morte em Guimarães Rosa - Ferreira, Fernanda Diniz (2023)
The present dissertation work consists of analyzing, in a comparative way, the short stories “A hora e vez de Augusto Matraga”, “Duelo” and “Os Irmãos Dagobé”, by João Guimarães Rosa. The first two stories are in Sagarana, the author's debut work, published in 1946. The third story is part of the book Primeiras Estórias, published in 1962. The core of the analysis is, specifically, to understand how the tragic death of the modern character is configured in Guimarães Rosa's short stories, as well as to contribute to the critical reading of the relationship between the tragic error and the destiny of the protagonists. It is observed that the beautiful death, originating in classical literature, demonstrates permanence and influence in contemporary literature. In addition, the aim is to identify, in the light of certain Aristotelian categories, how the tragic outcome continues to characterize the action of literary characters today, thus contributing to critical research, expanding studies on modernity and tradition. The methodology used is of a bibliographical nature, with the immanent reading of the stories, based on theoretical conceptions that deal with the chosen category or that have some relation with it. Thus, we prioritize the studies of Jean-Pierre Vernant (1977, 2022), among others that follow the same bias, such as: Marques Júnior (2008, 2013), Luna (2012), Campos (2000), which dialogue directly with the proposed analysis of this research.